Culturally adapted trauma-focused CBT-based guided self-help (CatCBT GSH) for female victims of domestic violence in Pakistan: feasibility randomized controlled trial. Issue 1 (30th January 2021) - Latif, Madeeha; Husain, M. Ishrat; Gul, Mirrat; Naz, Saiqa; Irfan, Muhammad; Aslam, Muhammad; Awan, Falahat; Sharif, Ayesha; Rathod, Shanaya; Farooq, Saeed; Ayub, Muhammad; Naeem, Farooq
Abstract: Background: Cognitive behaviour therapy (CBT), self-help and guided self-help interventions have been found to be efficacious and cost effective for victims of trauma, but there are limited data from low- and middle-income countries on culturally adapted interventions for trauma. Aims: To investigate the feasibility and acceptability of culturally adapted trauma-focused CBT-based guided self-help (CatCBT GSH) for female victims of domestic violence in Pakistan. Method: This randomized controlled trial (RCT) recruited 50 participants from shelter homes in Karachi and randomized them to two equal groups. The intervention group received GSH in nine sessions over 12 weeks. The control group was a waitlist control. The primary outcomes were feasibility and acceptability. Secondary outcomes included Impact of Event Scale-Revised (IES-R), Hospital Anxiety and Depression Scale (HADS) and the WHO Disability Assessment Schedule 2 (WHO DAS 2). Assessments were carried out at baseline and at 12 weeks. Results: Out of 60 clients who met DSM-5 criteria for post-traumatic stress disorder (PTSD), 56 (93.3%) agreed to participate in the study. Retention to the intervention group was excellent, with 92% (23/25) attending more than six sessions. Statistically significant differences were noted post-intervention in secondary outcomes in favour of the intervention. Conclusions: A trial of CatCBT GSH was feasible and the intervention was acceptable to Pakistani women who had experienced domestic violence. Furthermore, it may be helpful in improving symptoms of PTSD, depression, anxiety and overall functioning in this population. The results provide a rationale for a larger, confirmatory RCT of CatCBT GSH.